2015
DOI: 10.1155/2015/132326
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of N-Glycolyl GM3 Ganglioside Expression in Non-Small Cell Lung Carcinoma Patients: New Evidences

Abstract: The prognostic role of N-glycolyl GM3 ganglioside (NeuGcGM3) expression in non-small cell lung carcinoma (NSCLC) still remains controversial. In this study, the NeuGcGM3 expression was reevaluated using an increased number of NSCLC cases and the 14F7 Mab (a highly specific IgG1 raised against NeuGcGM3). An immunohistochemical score integrating the percentage of 14F7-positive cells and the intensity of reaction was applied to reassess the relationship between NeuGcGM3 expression, some clinicopathological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
(65 reference statements)
4
26
0
Order By: Relevance
“…Moreover, it has been reported that upregulated expression of mucins, such as MUC2 and MUC5AC, bind with EGFR and activate the Ras/Raf pathway [38,39]. In line with this, our group previously reported that the dual expression of EGFR and its ligand the EGF is related with increased cell proliferation and with a more aggressive behavior of NSCLC [16].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, it has been reported that upregulated expression of mucins, such as MUC2 and MUC5AC, bind with EGFR and activate the Ras/Raf pathway [38,39]. In line with this, our group previously reported that the dual expression of EGFR and its ligand the EGF is related with increased cell proliferation and with a more aggressive behavior of NSCLC [16].…”
Section: Discussionsupporting
confidence: 71%
“…Briefl y, the slides were pre-treated with 0.4% pepsin in 0.1N hydrochloric acid solution at 37°C for 30 minutes. Afterward, the tissues were incubated with ior egf/ r3 Mab (anti-EGFR) and CB-EGF1 (anti-EGF ligand) in a humid chamber for 1h at room temperature followed by a rabbit anti- were grouped as follow: low expression (scores < 150) and high expression (scores ≥ 150) as it was previously described in [16] ( …”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest that it is a frequent phenomenon and thus may support diagnostic considerations. Recently, our colleagues at CIM confirm that the expression of NeuGcGM3 or EGFR alone was associated with poor OS in NSCLC patients [ 9 ]. However, the expression of both targets in the same tumor sample was related with an even poorer prognosis in these patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many human tumors express NeuGcGM3 ganglioside [ 2 7 ]. The expression of NeuGcGM3 have been associated with a worse prognosis in colon [ 8 ] and lung cancer [ 7 , 9 ]. Differential association between EGFR signaling pathway and GM3 ganglioside expression has been reported [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This binding may provoke egFr system activation mediated by the epidermal growth factor ligand (egF). Activation of EGF in the presence of over expressed NeuGcGM3 constitutes a more aggressive immunophenotype in nonsmall cell lung cancer (NsCLC) [10] . Combination of antiegF plus anti-NeugcgM3 immunotherapies are currently under investigation [11] .…”
Section: Introductionmentioning
confidence: 99%